PEMBERDAYAAN TEKNOLOGI PERTANIAN DALAM MENINGKATKAN PENGHASILAN PETANI DI DESA AIR MANGGA INDAH KECAMATAN OBI KABUPATEN HALMAHERA SELATAN - Dailangi, Devi (Universitas Sam Ratulangi, 2016)
Village of Air Mangga Nndah Kecamatan Obi Kabupaten Halmahera Selatan provinsi Maluku Utara is one of the undergo development very rapidly since 2002-2015. But the triggering factor is position or the village of Air Mangga Indah accessible from the district capital. The occupation of the not only hang on agriculture course. The number of people labor as a farmer in Dusun Timur 183 who works as farmers in Dusun Barat 250 people. Habit of farming , the farmers follow the rainy season has been held since first until now there is no effort to change agriculture .This study attempts to see how a continuation of the district government more specifically of agriculture department in Kabupaten Halmahera Selatan for the farmers in the village Air Mangga Indah.This research used the a qualitative methodology, through the data collection and data processing by means of observation and interview. The district, province, and central government has tried to empower the community as a step improve the result farmers especially farmers nutmeg, rice fields and palm plantations them in the village Air Mangga Indah, but not get the maximal result. Keywords: farmer, agriculture, triggering